Pengembangan Aplikasi RT Pintar Berbasis Mobile Menggunakan Framework Flutter Dan Design Pattern MVC (Studi Kasus RT. 15 Perumnas Batu Ampar) - Muhammad Rafly Raihan Sumardi; Tegar Palyus Fiqar; Bowo Nugroho (Teknomatika, 2024)
Obstacles that are often encountered in channeling complaints and gaining access to community services and information are common problems in the village or RT environment. Even though the technology era should have overcome this problem, in fact the lack of application of technology in the aspect of community involvement has caused this problem to continue. The government is currently promoting the Smart City concept in various sectors, further emphasizing the urgency of implementing technology at this time. To overcome this challenge, the authors conducted research to develop a mobile-based application that includes complaints, public services, and access to information. The development framework used is Flutter and Dart which are programming languages suitable for mobile applications. In addition, the MVC (Model View Controller) design pattern is used to create structured and organized applications and facilitate future application development. In the application development process for this smart RT, GetX state management is implemented. The waterfall model SDLC (Software Development Life Cycle) approach is applied in the development stage. With the presence of this application solution, it is hoped that it will be able to provide convenience to the public in submitting complaints to related parties and accessing community services and information.